Adoption of sustainable forest management practices in Bolivian timber concessions: a quantitative assessment - Boscolo, M.; Snook, Laura K.; Quevedo, L. (2009)
Bolivia implemented an extensive reform of their forestry sector during the 1990s. Starting five years later, we evaluated the degree of adoption of sustainable forest management practices (SFM) by timber concessionaires in Bolivia and investigated the factors influencing their adoption. Data were obtained from surveys that quantified the level of adoption of 11 SFM practices in 23 concessions. The study revealed that concessionaires adopted some practices more than others. It found that regulation plays a critical role in promoting adoption. Adoption of SFM practices was also more frequent among operators that had been in the forestry business for a longer time, had larger concessions, harvested and processed larger volumes, utilized a wider set of species, were located closer to markets, had received more technical assistance, had trained their employees, and had made other investments. The owners' perception that SFM practices contributed to ecological sustainability was also an important factor in their decision to adopt these practices.